2020
DOI: 10.20944/preprints202002.0162.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drivers and Barriers for Successful Special Economic Zones (SEZs): Case of SEZs under China Pakistan Economic Corridor

Abstract: Over the last three decades, special economic zones (SEZs) have given new impetus to the ever-growing export-oriented industrialization in developing countries. Where various economies have benefited from SEZs, many zones have ended up becoming enclaves with trifling advantage. The SEZs in Pakistan have experienced the same fate and failed to contribute to exports, employment and creating linkages with the domestic economy. Recently under China Pakistan Economic Corridor (CPEC), SEZs are proposed to be set up … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Using the same working mechanism and policy approach in all SEZs in Indonesia has not been able to provide the same level of success. Previous studies reported In developing SEZs that in developing SEZs, a different approach is needed, based on the advantages and characteristics of each region and focusing more on competitiveness than fiscal incentives (Neem al, 2020), suitability of the type of SEZ focus on human resources skills and local innovation capacity (Frick & Rodriguez-Pose, 2019), a dynamic evolutionary strategy that is open to change in economic conditions and future development challenges (Aggarwal, 2019), also government high commitment and the ability for coordination and collective action (Darmastuti al, 2018). So, it is essential to develop a good strategy for developing special economic zones based on the scientific views of experts and the characteristics of each region, especially from a cultural aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same working mechanism and policy approach in all SEZs in Indonesia has not been able to provide the same level of success. Previous studies reported In developing SEZs that in developing SEZs, a different approach is needed, based on the advantages and characteristics of each region and focusing more on competitiveness than fiscal incentives (Neem al, 2020), suitability of the type of SEZ focus on human resources skills and local innovation capacity (Frick & Rodriguez-Pose, 2019), a dynamic evolutionary strategy that is open to change in economic conditions and future development challenges (Aggarwal, 2019), also government high commitment and the ability for coordination and collective action (Darmastuti al, 2018). So, it is essential to develop a good strategy for developing special economic zones based on the scientific views of experts and the characteristics of each region, especially from a cultural aspect.…”
Section: Introductionmentioning
confidence: 99%